IMPACTO DEL TURISMO VIVENCIAL EN EL DEPARTAMENTO DEL CUSCO CASO: PROVINCIA DE ANTA, DISTRITO DE MOLLEPATA - Ugarte Casafranca, Walter David (2013)
Mollepata is a district located in the province of Anta, Región Cusco, Peru. Since the efforts to enhance the ruins of Choquequirao, considered the “Machu Picchu sacred sister” and Quillarumiyoc archaeological complex, have developed incentive programs for alternative tourism in the form of experiential tourism. In this town we can find also notables cultural resources like thefestivitie of “Señor de la Exaltación”,and the one of the “Holy Cross of Tillca”. Mollepata has a splendid agricultural production and tours that offers to the visitors a variety of experiences. This district receives around 27,000 tourists a year (according to the Regional Directorate of Culture), which remains one or two days at the site since its objective is to reach Machu Picchu. However, it has shortcomings at the level of basic services infrastructure that hinder their development.